The Clinical Course of COVID-19 in the Outpatient Setting: A Prospective Cohort Study. (5th January 2021) - Blair, Paul W; Brown, Diane M; Jang, Minyoung; Antar, Annukka A R; Keruly, Jeanne C; Bachu, Vismaya S; Townsend, Jennifer L; Tornheim, Jeffrey A; Keller, Sara C; Sauer, Lauren; Thomas, David L; Manabe, Yukari C; et al.
Abstract: Background: Outpatient coronavirus disease 2019 (COVID-19) has been insufficiently characterized. To determine the progression of disease and determinants of hospitalization, we conducted a prospective cohort study. Methods: Outpatient adults with positive reverse transcription polymerase chain reaction results for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were recruited by phone between April 21 and July 23, 2020, after receiving outpatient or emergency department testing within a large health network in Maryland, United States. Symptoms were collected by participants on days 0, 3, 7, 14, 21, and 28, and portable pulse oximeter oxygen saturation (SaO2 ), heart rate, and temperature were collected for 15 consecutive days. Baseline demographics, comorbid conditions, and vital signs were evaluated for risk of subsequent hospitalization using negative binomial and logistic regression. Results: Among 118 SARS-CoV-2-infected outpatients, the median age (interquartile range [IQR]) was 56.0 (50.0–63.0) years, and 50 (42.4%) were male. Among individuals in the first week of illness (n = 61), the most common symptoms included weakness/fatigue (65.7%), cough (58.8%), headache (45.6%), chills (38.2%), and anosmia (27.9%). Participants returned to their usual health a median (IQR) of 20 (13–38) days from symptom onset, and 66.0% of respondents were at their usual health during the fourth week of illness. Over 28 days, 10.9% presented to the emergency department and 7.6% required hospitalization. The area under the receiver operating characteristics curve for the initial home SaO2 for predicting subsequent hospitalization was 0.86 (95% CI, 0.73–0.99). Conclusions: Symptoms often persisted but uncommonly progressed to hospitalization among outpatients with COVID-19. Home SaO2 may be a helpful tool to stratify risk of hospitalization.